Spiritual perspective and coping with death in the elderly in central Mexico - Guerrero Castañeda, Raúl Fernando (2022)
Objective: To analyze the relationship between spiritual perspective and coping with death in elderly people in the center of Guanajuato, Mexico. Methods: Quantitative, correlational, cross-sectional study, the selection criteria were elderly people aged 60 years and older, attendees of two gerontological centers. Convenience sampling with n=133. The Spiritual Perspective Scale, Bugen's Coping with Death Scale and a sociodemographic data form were used for data collection. Informed consent was signed. The data were analyzed by descriptive statistics, the study variables by Spearman correlation through SPSS version 25. Results: The Spiritual Perspective obtained a mean score of 50.86 and the Bugen scale of 145.65 points. Spearman correlation was performed where r=.375 and p=.000 (p<0.05) were obtained, giving a positive correlation between the study variables. Overall conclusion: A positive and statistically significant correlation was found between spiritual perspective and coping with death. Spirituality has a positive influence on how death is accepted since it is a tool that gives direction to the mourning process, generating feelings of hope, inner renewal and meaning in the elderly; therefore, the greater the spiritual perspective, the better the coping with death.